2021
DOI: 10.3846/jeelm.2021.14123
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Association Between Implementation of Iso 14031 Guidelines and Iso 14001 Certification by Industrial Sector in Saudi Arabia

Abstract: Conflicting research results regarding the application of environmental management systems on the environmental performance of industrial organizations between positive, negative, and no effect made studying this relationship a complex research problem. This study aimed to assess the extent of the commitment of industrial organizations in Saudi Arabia in applying ISO 14031:2013 guidelines to evaluate environmental performance and to study the association between the guideline implementation by ISO 14001:2015 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
(62 reference statements)
0
5
0
Order By: Relevance
“…A number of studies have demonstrated the advantages that firms may achieve by adopting ISO 14001; most of them categorize the benefits as environmental management (EM), environmental indicators (EIs), and environmental awareness and social aspects (EA) [2,3]. Unfortunately, ISO 14001 literature does not agree on the effect of adopting the standard on the environment [4]. Furthermore, few research works have investigated the drawbacks of implementing the standard and showed that the cost of adopting ISO 14001 could be high [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have demonstrated the advantages that firms may achieve by adopting ISO 14001; most of them categorize the benefits as environmental management (EM), environmental indicators (EIs), and environmental awareness and social aspects (EA) [2,3]. Unfortunately, ISO 14001 literature does not agree on the effect of adopting the standard on the environment [4]. Furthermore, few research works have investigated the drawbacks of implementing the standard and showed that the cost of adopting ISO 14001 could be high [5].…”
Section: Introductionmentioning
confidence: 99%
“…While some researchers view a positive relationship between adopting ISO 14001 and business EIs, others argue that there is no effect between ISO 14001 certification and some EIs [4]. Regarding the EM dimension, it includes four benefits, rigor and effectiveness of practices (EM01), regulatory compliance (EM02), greener supply chain (EM03), and documentation control (EM04) [3].…”
Section: Introductionmentioning
confidence: 99%
“…It takes the level of 1 when the company is ISO 14001certified and the level of 0 if the company is not certified. The explanatory variables represent the guidelines outlined in ISO 14031 (see the measuring tool given in [3]). The model was developed and evaluated based on an α of 0.05 in terms of fit measures, model coefficients, and predictive measures.…”
Section: Resultsmentioning
confidence: 99%
“…To scale EPEs in the Saudi industry, ISO 14031 was utilized. A questionnaire that was scaled as either 0 or 1, as listed in [3], was developed based on the requirements of the ISO 14031 standard and emailed to the selected companies. The questionnaire constructs comprised 13 items characterized by three descriptor variables: utilizing information and data, planning for EPEs and reviewing and improving EPEs [45].…”
Section: Methodsmentioning
confidence: 99%
“…The implementation of an EMS improves the environmental performance of the organization by implementing better technologies, which include, among others, the protection of natural resources [38]. Moreover, the implementation and certification of an EMS in accordance with the ISO 14001 standard contributes to reducing the amount of waste generated [39]. ISO 14001 contains requirements whose application in an organization allows for minimizing the negative impact on the environment by reducing pollutants and emissions [40].…”
Section: The Circular Economy In Organizations-management Systems And...mentioning
confidence: 99%